Recent Advances in Clinical Nutrition in Stroke Rehabilitation - Yoshimura, Yoshihiro (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Stroke is a common cause of death and disability worldwide. Malnutrition is prevalent in stroke rehabilitation patients, and has serious negative effects on outcomes. In addition, there is growing interest in new concepts related to malnutrition, such as sarcopenia, frailty, cachexia, chronic inflammation, dysphagia, and oral problems, all of which contribute to a poor prognosis. Therefore, it is necessary to assess nutritional status early and, if needed, provide appropriate nutritional interventions to improve patient outcomes. A multidisciplinary approach is strongly recommended in this setting; as such, high-quality clinical evidence regarding clinical nutrition in stroke rehabilitation is needed. This reprint updates our knowledge of clinical nutrition for stroke patients and includes interesting studies on topics including nutrition and weight management in the early stages of stroke, the relationship between frailty and improved physical function, weight gain by providing stored energy, physical activity and diet quality, L-carnitine and cognitive levels, and the prediction of stroke prognosis using temporal muscles. The Guest Editor hopes that this reprint will help provide clinicians with up-to-date knowledge of nutritional management in stroke rehabilitation.